SOCIOECONOMIC DATA VALIDATION ASSISTANCE FOR ACCURATE SOCIAL ASSISTANCE TARGETING IN GAMPONG TUNGKOP, ACEH BESAR - Lidyana Dinda; Aulia Khairullah; Indra Akbar; Natasya Amelia Yosa (PT. ROCE WISDOM ACEH, 2026)
The effectiveness of social assistance targeting is strongly influenced by the quality and timeliness of community socioeconomic data. Changes in employment, income, domicile, family composition, and asset ownership may cause recorded information to no longer reflect actual conditions. This community engagement program aimed to assist the verification and validation of the National Unified Socioeconomic Data (Data Tunggal Sosial dan Ekonomi Nasional-DTSEN) to improve the accuracy of social assistance beneficiary proposals in Gampong Tungkop, Darussalam District, Aceh Besar Regency. The program employed a descriptive-participatory approach using the Participatory Rural Appraisal method and involved 23 participants, including village officials, social data administrators, members of the tuha peut, community leaders, residents’ representatives, and the implementation team. Data were collected through participatory observation, document review, group discussions, village deliberations, and documentation and were subsequently analyzed using descriptive and thematic approaches. The results showed that the assistance program improved participants’ shared understanding of the functions of DTSEN, welfare decile classifications, and procedures for proposing and updating data. The village deliberation also facilitated clarification of residents’ socioeconomic conditions, identification of data requiring administrative correction or field verification, and formulation of follow-up recommendations for the village government. These findings indicate that participatory data verification can strengthen data transparency, accuracy, and timeliness. However, the results of this program do not constitute the final determination of social assistance beneficiaries, as such decisions remain subject to applicable regulations and the authority of the relevant government institutions.